A New Control Method to Reduce the Low-Frequency Output Current Ripple of AC-DC Converters by Using Virtual Inductor - Dahono, Pekik Argo (Journal of Engineering and Technological Sciences, 2012)
A new concept of virtual inductorÂ to reduce the low-frequency dc output current ripple of ac-dc converters is introduced in this paper. Virtual inductor is defined as an additional control algorithm that changes the system behavior into the one that has an additional inductor connected on it. The virtual nature of the inductor makes the inductance can be designed without weight and volume restrictions. How to use the virtual inductor to improve the performance of converter current controllerÂ is discussed in this paper. Several simulated and experimental results are included to show the validity of the proposed concept.